Influence of the Metal Migration From Screen-and-Fired Terminations on the Electrical Characteristics of Thick-Film Resistors. (1977) - Cattaneo, A.; Cocito, M.; Forlani, F.; Prudenziati, M.
Abstract : The electrical characteristics of ruthenium-based thick-film resistors with different conductive terminations (PtAu and Ag based compositions) and with different aspect ratios were examined. The purpose is to understand the effects of resistivity decrease and TCR variation caused by the migration of metal particles from the terminations into the resistor film. The majority of the data were collected by using silver-based terminations since Ag diffusion processes, and then the relevant electrical effects, are emphasized. Scanning electron microscopy, electron microprobe analysis and X-ray diffraction analysis have been used to analyze the diffusion processes and the thick-film microstructures. It is shown that the experimental data is simply explained by a conduction model which assumes percolative tunneling of electrons through conductive grains embedded in the glass matrix of the resistors. Using simple hypotheses the model theory gives a good quantitative fit of the experimental results.